The application of eDNA for monitoring of the great crested newt in the UK - Rees, Helen C.; Bishop, Keith; Middleditch, David J.; Patmore, James R.M.; Maddison, Ben C.; Gough, Kevin C. (Wiley, 2014)
Current ecological surveys for great crested newts are time-consuming and expensive and can only be carried out within a short survey window. Additional survey methods which would facilitate the detection of rare or protected species such as the great crested newt (Triturus cristatus) would be extremely advanta- geous. Environmental DNA (eDNA) analysis has been utilized for the detection of great crested newts in Denmark. Here, the same methodology has been applied to water samples taken from UK ponds concurrently with conventional field surveying techniques. Our eDNA analysis exhibited an 84% success rate with a kappa coefficient of agreement between field and eDNA surveys of 0.86. One pond determined to be negative for great crested newt by field survey was positive by eDNA analysis, revealing the potential for improved detection rates using this methodology. Analysis of water samples collected in late summer indicates that eDNA analysis could be used to detect great crested newt after the optimal survey window for current field techniques had passed. Conse- quently, eDNA analysis could augment currently stipulated techniques for great crested newt surveying as a relatively quick and inexpensive tool for collecting great crested newt presence and distribution data within the UK instead of or prior to full field surveys.